Carbon blacks having an STSA of 80-150 m2 / g, an OAN of at least 180 mL / 100 g, and a COAN of at least 110 mL / 100 g, and rubber compounds incorporating same.

Carbon blacks with defined STSA, OAN, and COAN properties address the trade-off issues in elastomer compositions, improving hysteresis and stiffness, thus reducing rolling resistance and enhancing fuel efficiency.

JP7619761B2Active Publication Date: 2025-01-22CABOT CORP
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2019560161
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-05-03
Filing Date
2018-04-27
Publication Date
2025-01-22
Estimated Expiration
2038-04-27

AI Technical Summary

Technical Problem

Existing carbon blacks used in elastomer compositions often enhance some properties while detracting from others, leading to unfavorable trade-offs such as increased hysteresis and reduced stiffness.

Method used

Development of carbon blacks with specific properties including STSA of 80-150 m²/g, OAN of at least 180 mL/100g, and COAN of at least 110 mL/100g, which improve hysteresis and maintain stiffness in rubber compositions.

Benefits of technology

These carbon blacks reduce unfavorable trade-offs by enhancing hysteresis and maintaining stiffness, contributing to lower rolling resistance and improved fuel efficiency in tires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619761000012
    Figure 0007619761000012
  • Figure 0007619761000013
    Figure 0007619761000013
  • Figure 0007619761000001
    Figure 0007619761000001
Patent Text Reader

Abstract

Carbon blacks such as high-structure reinforcing grade carbon black are described. This carbon black may have the following properties: a statistical thickness specific surface area (STSA) in the range of 80 m 2 / g to 150 m 2 / g, an oil absorption number (OAN) of at least 180 mL / 100 g, and a compressed oil absorption number (COAN) of at least 110 mL / 100 g. Rubber compounds incorporating the carbon black are also described.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to carbon black and rubber compounds incorporating carbon black. [Background technology]

[0002] Carbon black is used to modify the mechanical, electrical, and optical properties of compositions. Carbon black and other fillers are utilized as pigments, fillers, and / or reinforcing agents in the formulation and preparation of compositions used in rubber, plastic, paper, or textile applications. The properties of the carbon black or other fillers are important factors in determining various performance characteristics of these compositions. An important application of elastomeric compositions relates to the manufacture of tires, where additional ingredients are often added to impart specific properties to the final product or its components. Carbon black is used to modify the functional properties, electrical conductivity, rheology, surface properties, viscosity, appearance, and other properties of elastomeric compositions and other types of compositions. As mentioned above, carbon black and other fillers can provide reinforcement benefits to various materials, including elastomeric compositions. In addition to the traditional filler attributes, it is desirable to provide a filler that can improve one or more elastomeric properties, such as hysteresis, abrasion resistance, or stiffness. However, in some elastomeric compositions that have used carbon black or other fillers in the past, the filler has typically improved one property but at the expense of another. Thus, there is a continuing need to provide fillers for elastomeric compositions that can enhance elastomeric properties, preferably without the expense of another property. Summary of the Invention

[0003] The focus of this invention is to provide a new class of carbon blacks that have a unique combination of carbon black properties. Another focus of the present invention is to provide carbon blacks which, when present, enhance one or more beneficial properties in a rubber or other elastomeric composition without significantly impairing another property thereof. It is a further focus of the present invention to provide carbon blacks which, when present, can impart a beneficial balance of properties to a rubber composition. Another focus of the present invention is to provide high structure carbon black which, when present, can have the ability to improve hysteresis while maintaining stiffness of the rubber composition.

[0004] It is a further focus of the present invention to provide high structure carbon blacks that can be used in energy storage devices and other electrical or electrochemical components and devices, such as electrodes (e.g., positive electrodes in lithium ion batteries) and capacitors (e.g., electrochemical capacitors). Another object of the present invention is to provide a rubber compound modified with the above carbon black. Additional objectives and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by the practice of the invention. The objectives and other advantages of the invention will be realized and attained by means of the elements and combinations particularly pointed out in the description and appended claims.

[0005] To achieve these and other advantages, and in accordance with the purpose of the present invention, as embodied and broadly described herein, the present invention provides a method for manufacturing a 80-150m 2 / g, an oil absorption number (OAN) of at least 180 mL / 100 g, and a crushed oil absorption number (COAN) of at least 110 mL / 100 g. The present invention further relates to a rubber compound comprising at least one polymer and the above carbon black. The rubber compound may be a vulcanized rubber composition, a vulcanizable rubber composition, or an uncured rubber composition. It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are intended to provide further explanation of the invention as claimed. The accompanying drawings, which are incorporated in and constitute a part of this application, illustrate some of the features of the present invention and, together with the description, serve to explain the principles of the invention. [Brief description of the drawings]

[0006] [Figure 1] FIG. 1 illustrates a cross-sectional view of a carbon black reactor that can be used to produce carbon black according to an example of the present application. [Diagram 2] FIG. 2 shows a cross-sectional view of another related carbon black reactor that can be used to produce carbon black in accordance with an example of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention relates to carbon black and rubber compositions containing carbon black. The carbon black of the present invention can be a reinforcing grade carbon black. The carbon black of the present invention, having analytical properties within the specified ranges, can impart improved reinforcement and low hysteresis to the rubber composition while maintaining stiffness and electrical conductivity, avoiding or reducing adverse trade-offs in overall properties. The hysteresis of a compound refers to the difference between the energy applied to deform the rubber compound and the energy released when the rubber compound recovers to its initial, undeformed state. For example, a tire with a lower hysteresis value can reduce rolling resistance and therefore the fuel consumption of the vehicle utilizing the tire. In tire components such as carcasses, adequate stiffness must be maintained for physical structure and performance. The carbon black of the present invention can be used in non-tread tire components at lower loadings while maintaining stiffness, compared to standard carbon blacks used in this application (e.g., N300, N500, or other "N" series carbon blacks used in tire carcass or sidewall materials).

[0008] There is significant regulatory and environmental pressure to improve vehicle fuel economy. Tires play a key role in determining the fuel consumption of passenger cars, light trucks, and heavy truck vehicles. Compared to the tread, which provides wear and grip performance, the remainder of the carcass or other non-tread components have different functions and therefore tend to have different optimal filler materials. The carbon black of the present invention can be used in tire components such as the carcass or other non-tread parts to replace N300, N500, or other N series carbon blacks used in such components. As shown, the carbon black of the present invention allows the use of carbon black in reinforced tire components or other rubber components to reduce hysteresis, but still maintain stiffness and electrical conductivity. The present invention can provide a significant high structure carbon black that can negate (avoid or reduce) the trade-off between loss of stiffness and improved (reduced) hysteresis. As shown by the results of the experimental studies disclosed in the Examples herein, in rubber compound applications where maximum tan δ (delta) can be considered a metric of rolling resistance contribution, the carbon blacks of the present invention provide modified rubber compounds with stiffness G'(10%) (MPa) and hysteresis tan δ that are at least about 5% greater, or at least about 10% greater, or at least about 15% greater, or at least about 20% greater, or at least about 25% greater, or more, than similar compositions of comparable hardness containing comparable commercially tested carbon blacks, such as VULCAN® M carbon black, VULCAN® 6 carbon black or PROPEL® E6 carbon black, VULCAN® 10H carbon black, VULCAN® 7H carbon black, or other N100, N200, or N300 series carbon blacks, or other ASTM carbon blacks. 最大 The ratio of can provide stiffness and hysteresis.

[0009] In view of these improving effects, the carbon black of the present invention can be advantageously used in rubber compounds. Rubber compounds that can benefit from the carbon black of the present invention can include extruded, molded, or cast rubber products. The rubber products can be, for example, tires, tire components, hoses, tubes, belts, seals, liners, or other rubber products. Tire components that can be reinforced with the carbon black of the present invention include carcasses, sidewalls, bead encapsulation rubber, belts, treads, or other tire parts. Optionally, non-tread components such as tire carcasses, sidewalls, bead encapsulation rubber, or other tire parts can be modified with the carbon black of the present invention.

[0010] Structure is a measure of the complexity of the carbon black agglomerates. In the present invention, the structure of the carbon black is characterized by the oil absorption and crushed oil absorption measured on the material. The structure characterized by oil absorption is determined as the Oil Absorption Number (OAN) as determined by ASTM D2414-13a, where the OAN value is expressed as milliliters of oil per 100 grams of carbon black. The OAN value is also known as the dibutyl phthalate absorption number (DBP). Crush OAN (COAN) measurement is used to determine the COAN value of the carbon black. The COAN value is the OAN value of the carbon black determined after controlled compression and is expressed as milliliters of oil per 100 grams of carbon black after compression. The COAN value is also known as the dibutyl phthalate absorption number (CDBP, 24M4DBP). As used herein, unless otherwise specified, the COAN value is based on a modified version of ASTM standard D3493-13a. For the COAN measurements disclosed herein, the procedure of ASTM test method D3493-13a is used with a modification in which 15 grams of carbon black are crushed in a compression cylinder as described in the procedure of the test method, and then 10 grams of these 15 grams of crushed matter are tested in an absorptometer used to determine oil absorption number as per the procedure of the ASTM test method, and then the results are scaled to 100 grams of material. The OAN and COAN values ​​determined according to the above ASTM standards also apply to values ​​determined according to the corresponding JIS standards (e.g., JIS K 6221).

[0011] In this application, the surface area of ​​carbon black is defined and determined according to ASTM standard D6556-10. As explained in ASTM standard D6556-10, this test method includes the determination of nitrogen surface area by the theory of multilayer gas adsorption behavior using the multipoint determination of Brunauer, Emmett, and Teller (Brunauer, Stephen; Emmett, PH; Teller, Edward (1938). "Adsorption of Gases in Multimolecular Layers". Journal of the American Chemical Society. 60 (2): 309-319) and the external surface area based on statistical thickness specific surface area (STSA). The total surface measurement (NSA measurement) is based on the BET theory, which includes the total surface area including micropores with a pore diameter of less than 2 nm (20 Å), while the external surface area based on statistical thickness specific surface area (STSA) is defined as the specific surface area accessible to rubber. As shown, the carbon blacks of the present invention are characterized by a property defined by the external surface area (STSA) value in combination with the OAN and COAN values ​​determined for the same material.

[0012] One option of the present invention is a) 80m 2 / g~150m 2 / g range of STSA, b) OAN ≥ 180 mL / 100 g, and c) COAN≧110mL / 100g The present invention provides a carbon black having the following properties: Another option is a) 90m 2 / g~150m 2 / g range of STSA, b) OAN ≥ 180 mL / 100 g, and c) COAN≧120mL / 100g The present invention provides a carbon black having the following properties: Another option is 100m 2 / g~150m2 / g range of said STSA; at least 200 mL / 100 g of said OAN; and At least 120mL / 100g of said COAN The present invention provides a carbon black having the following properties:

[0013] As an option, STSA, i.e., property a), is 80m 2 / g~150m 2 / g range, or 90m 2 / g~150m 2 / g range, or 100m 2 / g~150m 2 / g range, or 90m 2 / g~145m 2 / g range, or 95m 2 / g~145m 2 / g range, or 100m 2 / g~145m 2 / g range, or 90m 2 / g~140m 2 / g range, or 95m 2 / g~140m 2 / g range, or 100m 2 / g~140m 2 / g range, or 105m 2 / g~135m 2 / g range, or 110m 2 / g~130m 2 / g range, or 115m 2 / g~125m 2 / g or other values.

[0014] In one option, the OAN, i.e. property b), is at least 180 mL / 100 g, or at least 190 mL / 100 g, or at least 200 mL / 100 g, or at least 210 mL / 100 g, or at least 220 mL / 100 g, or at least 230 mL / 100 g, or in the range of 180 mL / 100 g to 320 mL / g, or in the range of 190 mL / 100 g to 320 mL / g, or in the range of 200 mL / 100 g to 320 mL / g, or in the range of 210 mL / 100 g to 320 mL / g, or in the range of 180 mL / 100 g to 310 mL / g. L / g range, or 190mL / 100g to 310mL / g range, or 200mL / 100g to 310mL / 100g range, or 210mL / 100g to 310mL / g range, or 180mL / 100g to 300mL / g range, or 190mL / 100g to 300mL / g range, or 200mL / 100g to 300mL / g range, or 210mL / 100g to 300mL / g range, or 220mL / 100g to 290mL / 100g range, or 230mL / 100g to 280mL / g range, or other values.

[0015] In one option, the COAN, i.e. property c), is at least 110 mL / 100 g, or at least 120 mL / 100 g, or at least 130 mL / 100 g, or at least 140 mL / 100 g, or in the range of 110 mL / 100 g to 160 mL / g, or in the range of 115 mL / 100 g to 160 mL / g, or in the range of 120 mL / 100 g to 160 mL / g, or in the range of 110 mL / 100 g to 155 mL / g, or in the range of 115 mL / 100 g to 155 mL / 100 g, or in the range of 115 mL / It may be in the range of 100g-155mL / g, or in the range of 110mL / 100g-150mL / g, or in the range of 115mL / 100g-150mL / g, or in the range of 120mL / 100g-150mL / g, or in the range of 110mL / 100g-145mL / g, or in the range of 115mL / 100g-145mL / g, or in the range of 120mL / 100g-145mL / g, or in the range of 125mL / 100g-145mL / 100g, or in the range of 130mL / 100g-140mL / g, or other values. The carbon black of the present invention can have any of the above values ​​for STSA, OAN, and COAN, i.e., properties a), b), and c), in any combination thereof. With regard to other properties that the carbon black of the present invention may have in addition to the properties described above for STSA, OAN, and COAN (i.e., properties a), b), and c)), these include, but are not limited to, one or more of the following additional properties:

[0016] d) Iodine adsorption number (ASTM-D1510-13) in the range of 85mg / g to 220mg / g, or in the range of 90mg / g to 220mg / g, or in the range of 100mg / g to 220mg / g, or in the range of 100mg / g to 210mg / g, or in the range of 85mg / g to 210mg / g, or in the range of 90mg / g to 210mg / g, or in the range of 100mg / g to 210mg / g, or in the range of 85mg / g to 200mg / g, or in the range of 90mg / g to 200mg / g, or in the range of 100mg / g to 200mg / g, or in the range of 110mg / g to 200mg / g, or in the range of 115mg / g to 190mg / g, or in the range of 120mg / g to 180mg / g, or other values.

[0017] e) a ratio of iodine adsorption number / STSA that is between 0.9 and 1.5, or between 0.95 and 1.5, or between 1.5, or between 0.9 and 1.45, or between 0.95 and 1.45, or between 1 and 1.45, or between 0.9 and 1.4, or between 0.95 and 1.4, or between 1 and 1.4, or between 0.9 and 1.35, or between 0.95 and 1.35, or between 1 and 1.35, or between 0.9 and 1.3, or between 0.95 and 1.3, or between 1.0 and 1.3, or between 1.05 and 1.25, or between 1.10 and 1.20, or other values. The ratio of iodine adsorption number / STSA distinguishes between unetched and etched carbon black, e.g., etched carbon black will have a larger ratio of iodine adsorption number / STSA. f) 70m 2 / g~200m 2 / g range, or 90m 2 / g~200m 2 / g range, or 80m 2 / g~170m 2 / g range, or 70m 2 / g~135m 2 / g range, or 50m 2 / g~140m 2 / g range, or 105m 2 / g~135m 2 / g range, or 110m 2 / g~130m 2 / g range, or 115m 2 / g~125m 2 / g range, or other values ​​of BET surface area.

[0018] g) ΔD of 75 nm or less, or 70 nm or less, or 65 nm or less, or 60 nm or less, or 55 nm or less, or 50 nm or less, or in the range of 40 nm to 75 nm, or in the range of 45 nm to 70 nm, or in the range of 50 nm to 65 nm, or in the range of 55 nm to 60 nm, or any other value 50 . h) a crystallite size (L) of 29 Å or less, or 27 Å or less, or 25 Å or less, or 23 Å or less, or 21 Å or less, or 19 Å or less, or 15 Å or less, or 13 Å or less, or 11 Å or less, or 10 Å or less, or in the range of 10 Å to 29 Å, or in the range of 13 Å to 27 Å, or in the range of 15 Å to 25 Å, or in the range of 17 Å to 23 Å, or other values; a ).

[0019] i) An average primary particle size in the range of about 8 nm to about 50 nm, or in the range of about 12 nm to about 24 nm, or in the range of about 13 nm to about 23 nm, or in the range of about 14 nm to about 22 nm, or in the range of about 15 nm to about 21 nm, or in the range of about 16 nm to about 20 nm, or other values.

[0020] j) Approximately 1mJ / m 2 ~about 15mJ / m 2 or about 2 mJ / m 2 ~about 13mJ / m 2, about 3mJ / m 2 ~about 12mJ / m 2 or about 4 mJ / m 2 ~about 11mJ / m 2 or about 5 mJ / m 2 ~about 10mJ / m 2 or other values ​​of surface energy. k) tint strength (ASTM-D3265-15a) in the range of 105% to 140%, or in the range of 110% to 140%, or in the range of 115% to 135%, or in the range of 120% to 130%, or other value.

[0021] The carbon black of the present invention can alternatively have a combination of properties a), b), and c) without other properties, or a combination including properties a), b), and c) and one or more of the additional predetermined properties d)-k), in any combination. For example, the carbon black of the present invention can have at least 1, 2, 3, 4, 5, 6, 7, or all 8 of properties d)-k) in addition to properties a), b), and c). The carbon black can have any combination of properties a)-k). The ΔD of property g) 50 can be measured according to the ISO 15825 method using a disk centrifuge photosedimentometry, model BI-DCP, manufactured by Brookhaven Instruments. Property i), the average primary particle size, can be determined by ASTM-D3849-14a. Property h), i.e., the crystallite size L a (i.e., the size of the ordered domains of microcrystalline carbon black as determined by Raman spectroscopy as disclosed in U.S. Pat. No. 9,287,565) and j), i.e., the surface energy, are disclosed in U.S. Pat. No. 9,287,565, which is incorporated herein by reference in its entirety. The other properties a)-f) and k) can be determined as described above or as shown in the examples herein.

[0022] The rubber compounds of the present invention can be prepared from the carbon black by compounding with any elastomer, such as elastomers useful in compounding carbon black. Any suitable elastomer can be compounded with the carbon black to provide the elastomeric compounds of the present invention. Such elastomers include, but are not limited to, polymers (e.g., homopolymers, copolymers, or terpolymers) of rubber, 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dimethyl-1,3-butadiene, acrylonitrile, ethylene, and propylene. Preferably, the elastomer has a glass transition temperature (Tg) in the range of about -120°C to about 0°C as measured by differential scanning calorimetry (DSC). Examples include, but are not limited to, styrene-butadiene rubber (SBR), natural rubber, polybutadiene, polyisoprene, and oil-extended derivatives thereof. Blends of any of the foregoing elastomers can also be used, as well as functional derivatives of these polymers.

[0023] Alternatively, rubbers suitable for use in the present invention include natural rubber and its derivatives, such as chlorinated rubber. The carbon black of the present invention can be used with the following synthetic rubbers: copolymers of about 10 to about 70% by weight styrene and about 90 to about 30% by weight butadiene, such as a copolymer of 19 parts styrene and 81 parts butadiene, a copolymer of 30 parts styrene and 70 parts butadiene, a copolymer of 43 parts styrene and 57 parts butadiene, and a copolymer of 50 parts styrene and 50 parts butadiene; polymers and copolymers of conjugated dienes, such as polybutadiene, polyisoprene, polychloroprene, and the like, as well as polymers and copolymers of such conjugated dienes and ethylene group-containing monomers copolymerizable therewith, such as styrene, methylstyrene, chlorostyrene, methyl ... Styrene, acrylonitrile, 2-vinyl-pyridine, 5-methyl 2-vinylpyridine, 5-ethyl-2-vinylpyridine, 2-methyl-5-vinylpyridine, alkyl substituted acrylates, vinyl ketones, methyl isopropenyl ketone, methyl vinyl ether, alpha methylene carboxylic acids and their esters and amides, such as copolymers with acrylic acid and dialkyl acrylic acid amides; also copolymers of ethylene with other higher alpha olefins, such as propylene, butene-1, and pentene-1, are suitable for use herein. Additional suitable elastomers will be readily apparent to the skilled artisan, given the benefit of this disclosure.

[0024] Alternatively, the rubber compound of the present invention may contain the elastomer(s) and the carbon black of the present invention, as well as a curative, a coupling agent, and optionally additional reinforcing fillers different from the carbon black of the present invention, various processing aids, extender oils, antidegradants, and / or other additives. In preparing the rubber composition, one or more curatives may be used, such as, for example, sulfur, sulfur donors, activators, accelerators, peroxides, and other systems used to effect vulcanization of the elastomer composition. The loading level of carbon black in the rubber compound may depend on the intended use of the composition. Alternatively, the amount of carbon black may be 1% to 90%, or 5% to 85%, or 10% to 80%, or 20% to 75%, or 25% to 70%, or 30% to 65%, or 35% to 60%, or other amounts, based on the total weight of the rubber compound.

[0025] The rubber compound incorporating carbon black and other ingredients can be produced by any suitable method. Methods can include dry mixing techniques, wet mixing techniques, methods using multi-stage mixing processes, or other methods for mixing and processing the ingredients, such as those disclosed in U.S. Patent Nos. 5,916,956, 6,048,923, 7,582,688, 8,586,651, and 8,536,249, which are incorporated herein by reference in their entirety. As indicated, the resulting rubber compound can be used to manufacture various elastomeric products, such as vehicle tire components (e.g., carcass, sidewall, bead rubber, tread), industrial rubber products, seals, timing belts, power transmission belts, and other rubber products.

[0026] Alternatively, the carbon black may be channel black, furnace black, and lamp black. The carbon black is preferably furnace carbon black. As a preferred option, the production of carbon black includes the use of a multi-stage carbon black reactor. As used herein, a "multi-stage reactor" is equipped with multiple feedstock injection locations, with one or more subsequent injection locations downstream of a first injection location. More preferably, the multi-stage reactor has at least two stages (2, 3, 4, or more stages) in which the introduction of at least two feedstocks (e.g., 2, 3, 4, or more feedstocks) generally occurs. 1 and 2 show exemplary sections of two related carbon black reactors that can be used to produce the carbon blacks of the present invention using a multi-furnace process taking into account the process conditions described herein.

[0027] The process conditions and reactor configurations for the production of the high structure carbon black of the present invention in both reactors shown in Figures 1 and 2 can include two transitions upstream of a complete quench where the carbon black producing feedstock is introduced (i.e., injected) and separated by a spacer tunnel with increased volume space to allow for the option of intermediate injection of quench water between the two transitions and / or the use of a water-cooled metal spacer tunnel. Carbon black can be produced in these reactors where the carbon black producing feedstock is introduced in a first transition (stage) and combined with a stream of hot gas to form a precursor, after a residence time in the spacer tunnel, subsequently a second carbon black producing feedstock is introduced downstream of that precursor in a second transition (stage) and then the reaction stream is quenched to terminate the reaction.

[0028] In reactor 2 of Figure 1, the transition sections are shown as 12 and 22, the spacer tunnel as 18, and the full quench location as 58. In reactor 2 shown in Figure 1, spacer tunnel 18 is lined with liner 19, which may be refractory brick. An intermediate partial quench can be injected into spacer tunnel 18 through recessed injection ports 24A or 24B, or both, in reactor 2 shown in Figure 1, by using an intermediate quench fluid, such as water or another quench fluid (e.g., nitrogen).

[0029] In the reactor 200 of FIG. 2, the transitions are shown as 212 and 220, the spacer tunnel as 180, and the complete quench location as 580. In the reactor 200 shown in FIG. 2, the spacer tunnel 180 is formed of water-cooled metal components arranged in a tubular shape. The spacer tunnel 180 can be, for example, a water-cooled, thermally conductive metal-walled enclosure, such as a metal tube structure with an integral water jacket through which cooling water can be continuously passed. The intermediate partial quench can be injected into the spacer tunnel 180 through one or more injection ports 240 in the reactor 200 shown in FIG. 2, for example, by using an intermediate quench fluid, such as water or other quench fluid. The injection ports 24A, 24B, or 240 can optionally be water-jacketed pipes that include a water outlet path and another path for flowing cooling water into the water injection probe.

[0030] The increased volume provided by the spacer tunnels between the transitions (12 and 22 in FIG. 1, 212 and 220 in FIG. 2) of these reactors (2, 200) allows for more recirculation and a longer residence time between the planes defined by the two feedstock injection locations at the transitions of the reactors, both of which enhance the carbon black's ability to develop as much structure as possible during each stage. Furthermore, after the second transition (22 in FIG. 1, 220 in FIG. 2), the diameter size of the reactor (50 in FIG. 1, 500 in FIG. 2) increases significantly, thereby maximizing the structure of the carbon black. Without wishing to be bound by any particular theory, the two related reactor geometries shown in FIGS. 1 and 2 can be used to create a series of exceptionally high structure carbon blacks, as characterized by OAN and COAN.

[0031] With regard to other features of the reactor 2 shown in FIG. 1, the reactor 2 includes a combustion chamber 10 in which a combustion gas (liquid or gaseous fuel) 13 is introduced and mixed with an oxidizer 15 (including, for example, oxygen, air) that is introduced into the chamber 10 through a port (not shown) and ignited by any method known in the art. The resulting stream of hot gas F flows through a frustoconical zone 11 and converges in diameter into a generally cylindrical zone that includes several successive tubular sections (12, 18, and 22). The carbon black-producing feedstock introduced at either transition (12, 22) can be introduced in any conventional manner, such as single or multiple streams. The introduction of the feedstock can be at any rate. In multiple streams, the velocity of each stream can be the same or different. In FIG. 1, feedstock injection ports 32 and 42 are located within the front and end tubular sections that define the first transition section 12 and the second transition section 22, respectively, with the second transition section 22 being located downstream of the first transition section 12. Although FIG. 1 shows a single feedstock injection port (32, 42) for each transition section (12, 22), typically more than one feedstock injection port is located circumferentially around each transition section 12 and 22, with multiple streams of feedstock 30 being injected into the first transition section 12 and multiple streams of feedstock 40 being injected into the second transition section 22. Any method capable of introducing the carbon black producing feedstock can be used. For example, the carbon black producing feedstock can be injected into the reactor at the transition section by multiple streams, which enter an interior region of the hot combustion gas stream at transition section 12 and the reaction stream at second transition section 22 to ensure rapid mixing and shearing of the carbon black producing feedstock and the combustion gas / reaction stream. As shown, spacer tunnel 18 is located between transition sections 12 and 22 .

[0032] In the configuration of FIG. 1, fuel is ignited in the combustion chamber 10 and the resulting flow is directed into a tunnel-like zone comprised of zones 12, 18, and 22 where it contacts a first charge of feedstock injection at the first transition 12. Subsequent flow into the spacer tunnel 18 allows for the above-mentioned recirculation and longer residence time between the feedstock injection locations before contacting a second charge of feedstock introduced at the second transition 22. As shown in FIG. 1, the spacer tunnel 18 may have a cylindrical section of constant diameter at its front end adjacent the first transition 12 and a conical refractory section at its rear end that contracts in diameter toward the second transition 22. An intermediate partial water quench or other quench fluid may be provided to the spacer tunnel 18 as shown. The gas / carbon black particle mixture exiting transition 22 then flows into one or more reactor zones (50, 52, and 54) of increased diameter and is then quenched, which may be lined with a liner 56 (e.g., one or more reactor zones of increased diameter are lined with refractory). Quenching is typically accomplished by water spray at a quench location 58, the distance of which may vary from transition 22. A quench 58, located at point 57, which injects quench fluid 59, may be utilized to quench the carbon black yielding feedstock. Q is the distance from the downstream end 55 of transition 22 to point 57, which varies according to the location of the quench, which may coincide with the beginning of reactor zone 50.

[0033] The operation of the reactor 200 shown in FIG. 2 may be substantially the same as the operation of the reactor 2 of FIG. 1, except for the above-mentioned differences in the configuration of the spacer tunnels located between the transitions. In the configuration of FIG. 2, fuel is ignited in the combustion chamber 110 and the resulting flow is directed to a tunnel-like zone consisting of zones 212, 180, and 220, where the fuel contacts the first charge of feedstock injection 320 at the first transition 212. Subsequent flow to the spacer tunnel 180 allows for the above-mentioned recirculation and longer residence time between the feedstock injection locations before contacting the second charge of feedstock 420 introduced at the second transition 220. As shown, an intermediate partial water quench or other quench fluid can be fed to the spacer tunnel 180. The gas / carbon black particle mixture exiting the transition 220 then flows into one or more reactor zones (500) of increased diameter and is then quenched at the quench location 580.

[0034] With respect to the intermediate quench fluid introduced into the spacer tunnel 18 of reactor 2 of FIG. 1 or the spacer tunnel 180 of reactor 200 of FIG. 2, the mass ratio of the amount of injection fluid (e.g., quench water) to the carbon black yielding feedstock introduced at the first transition (12, 120) can be relatively small compared to the feedstock fraction. Alternatively, the mass ratio of the amount of injection fluid (e.g., quench water) to the carbon black yielding feedstock introduced at the first transition (12, 120) can be from 0 to about 1:1, or from about 0.05:1 to about 1:1, or from about 0.1:1 to about 1:1, or from about 0.2:1 to about 0.5:1, or from about 0.3:1 to about 0.7:1, or from about 0.4:1 to about 0.8:1, or other amounts.

[0035] In Figures 1 and 2, the various D numbers represent the various internal diameter sizes of the reactor sections, and the various L numbers represent the various lengths of the reactor sections. As shown, Q is the distance from the end of the second transition to the final quench. Examples of these D, L, and Q parameters are described in the Examples section herein. Other values ​​may be used. The term "diameter" as used herein with respect to any zone or stage of a carbon black reactor refers to the hydraulic diameter (DH ), which is calculated from the formula: 4A / P, where A is the cross-sectional area and P is the perimeter.

[0036] With respect to the hot gas stream combined with the carbon black production feedstock, the hot gas stream can also be considered a hot combustion gas that can be produced by contacting a solid, liquid, and / or gaseous fuel with a suitable oxidant stream, such as, but not limited to, air, oxygen, or a mixture of air and oxygen. Alternatively, a preheated oxidant stream can be passed through without the addition of liquid or gaseous fuel. Examples of fuels suitable for use in contacting the oxidant stream to produce the hot gas include flammable gas, steam, or liquid streams such as natural gas, hydrogen, carbon monoxide, methane, acetylene, alcohol, or kerosene. It is usually preferred to use fuels that have a high content of carbon-containing components and especially hydrocarbons. The air to fuel ratio utilized to produce the carbon black of the present invention can be from about 0.6:1 to infinity, such as 1:1 (stoichiometric ratio) to infinity, or 0.6:1 to 10:1, or 1:1 to 10:1. As stated, the oxidant stream may be preheated to facilitate the production of the hot gas. Preferably, the hot gas stream is formed upstream of all points where the carbon black-yielding feedstock is introduced into the reactor.

[0037] The carbon black producing feedstock can be any conventional carbon black producing feedstock that results in the formation of carbon black. For example, any hydrocarbon material can be used. A suitable feedstock can be any carbon black producing hydrocarbon feedstock that is readily volatilizable under the reaction conditions. For example, unsaturated hydrocarbons such as acetylene; olefins such as ethylene, propylene, butylene; aromatics such as benzene, toluene, and xylene; certain saturated hydrocarbons; and other hydrocarbons such as kerosene, naphthalene, terpenes, ethylene tar, aromatic cycle stock, etc. can be used. Preferably, the introduction of the carbon black producing feedstock at the second (downstream) transition does not completely quench the reaction. The carbon black producing feedstock introduced at the second transition can be the same type of feedstock or a different feedstock than the carbon black producing feedstock introduced at the first (upstream) transition. Furthermore, the application of the additional feedstock to the pre-existing carbon black particles can be repeated any number of times until the reaction of the feedstock to carbon black is complete. Each time additional feedstock is added, the temperature of the entire reaction mixture typically decreases and the particle size of the carbon black increases. In this manner, the additional introduction of the feedstock may act as a partial quenching agent to cool the carbon black.

[0038] The total amount of carbon black producing feedstock introduced into the reactor (2, 200) can be split between the first transition section (12, 120) and the second transition section (22 and 220) based on feed rates (mass / time units) of about 15:85 to 85:15, or about 20:80 to 80:20, or 30:70 to 70:30, or 60:40 to 40:60, respectively. As an option, the carbon black producing feedstock introduced at the second transition section contains at least 15% by weight of the total amount of carbon black producing feedstock utilized during the entire process. The carbon black producing feedstock introduced at the second transition section may contain from about 15% to about 80% by weight of the total amount of carbon black producing feedstock utilized during the entire process. Other ranges include from about 25% to about 70% by weight or from about 30% to about 60% by weight of the total amount of carbon black producing feedstock utilized during the entire process.

[0039] As an alternative, the first and second transitions may have respective first and second temperature zones with a temperature difference relative to each other. In this alternative, the first and second temperature zones may have a temperature difference of 200° C. or more, preferably 300° C. or more. Suitable ranges for the temperature difference may be, for example, about 200° C. to about 900° C. or about 400° C. to about 700° C. Other temperature ranges for the temperature difference may be used. Typically, for this temperature difference, the first temperature zone has a higher temperature and the second temperature zone has a lower temperature, which results in a temperature difference, but this is only a preferred embodiment. The temperature difference may be achieved in various ways, such as the effect of the intermediate quench described above in the spacer tunnel, or by avoiding any further introduction of combustion gases, or by avoiding or minimizing the formation of combustion gases in the second temperature zone, or any combination of these. Other means may be used to achieve this difference. For example, a water jacket may be used around the reactor (or part thereof) when the carbon black-yielding feedstock is introduced at or after the second transition. In the alternative or combination, steam can be introduced at this point. Additionally or alternatively, other quenching agents, such as nitrogen, water, or other suitable quenching agents, can be used to effectuate the reduction in temperature at or after the second carbon black yielding feedstock is introduced. Preferably, there is no water jacket or other quenching device or means present in the first temperature zone in any of the embodiments of the invention, and preferably such quenching occurs immediately prior to, during, or immediately after the introduction of the carbon black yielding feedstock at the second transition.

[0040] After the mixture of hot combustion gases and carbon black-yielding feedstock is completely quenched, the cooled gas is passed downstream to any conventional cooling and separation means, thereby recovering the carbon black. Separation of the carbon black from the gas stream can be readily accomplished by conventional means, such as a settler, cyclone separator, or bag filter. With respect to completely quenching the reaction to form the final carbon black, any conventional means can be used to quench the reaction downstream of the introduction of the carbon black-yielding feedstock at the second transition, which are known to those skilled in the art. For example, a quench fluid can be injected, which can be water or other suitable fluid for stopping chemical reactions. The carbon black can be used as is, or can be pelletized or otherwise further processed or treated (e.g., surface modified).

[0041] The production of carbon black may further include the controlled introduction of at least one substance that is or contains at least one Group IA or Group IIA element (or ion thereof) of the periodic table. The charge of the metal ion may provide a repulsive force between individual carbon black particles. This repulsive force may keep the particles from agglomerating, thus reducing the overall structure of the carbon black. With this in mind, the presence of at least one Group IA or Group IIA element in the carbon black may be counterproductive to providing a very high structure carbon black. Optionally, small amounts of selected at least one Group IA or Group IIA element may be tolerated or even introduced in small amounts in one or more phases of the reaction to provide some limited tailoring of the structure, provided that the resulting carbon product still meets the OAN and COAN requirements specified herein. For example, at least one Group IA or Group IIA element is present in an amount of about 10 ppm or less, for example, about 5 ppm or less, about 2 ppm or less, about 1 ppm or less, about 0.5 ppm or less, about 0.2 ppm or less, or about 0.1 ppm. Preferably, at least one Group IA or Group IIA element is present in an amount of about 0 ppm. The material that is or contains at least one Group IA or Group IIA element can contain at least one alkali metal or alkaline earth metal, such as lithium, sodium, potassium, rubidium, cesium, francium, calcium, barium, strontium, or radium, or a combination thereof. The material can be a solid, a solution, a dispersion, a gas, a salt, or any combination thereof. If used, the material can be introduced before complete quenching. As indicated, the amount of Group IA or Group IIA metal-containing material, when used or otherwise permitted to be present, can be any amount so long as it results in the formation of a carbon black that still meets the above OAN and COAN values ​​specified for the structure.

[0042] Alternatively, the carbon black can be modified. For example, the carbon black of the present invention can include attached chemical groups and / or coupling agents to the surface, or can include adsorbed chemical groups thereon, or can have a coating on the carbon black surface (e.g., a chemical coating such as a silica coating or other coating), or can include an oxidized surface, or any combination thereof. The carbon black of the present invention can have one or more attached chemical groups, such as one or more organic groups. One process for attaching chemical groups to the carbon black can involve the reaction of at least one diazonium salt with the carbon black. Other methods of attaching chemical groups to the carbon black can be used. Chemical groups, as well as methods of attaching these groups to the carbon black, can include those shown in the following U.S. patents and publications, which are incorporated herein by reference in their entireties: Nos. 5,851,280, 5,837,045, 5,803,959, 5,672,198, 5,571,311, 5,630,868, 5,707,432, 5,554,739, 5,689,016, 5,713,988, 8,975,316, 9,388,300, WO 96 / 18688, WO 97 / 47697, and WO 97 / 47699. The carbon black of the present invention can have one or more chemical groups adsorbed thereon, such as one or more organic groups. Chemical groups, as well as methods for adsorbing these groups to carbon black, can include those set forth in US Pat. Nos. 8,975,316 and 9,175,150, which are incorporated herein by reference in their entireties.

[0043] Alternatively or additionally, a coupling agent can be used that can be or include one or more silane coupling agents, one or more zirconate coupling agents, one or more titanate coupling agents, one or more nitro coupling agents, or any combination thereof. Coupling agents include bis(3-triethoxysilylpropyl)tetrasulfane (e.g., Si69 from Evonik Industries, Struktol SCA98 from Struktol Company), bis(3-triethoxysilylpropyl)disulfane (e.g., Si75 and Si266 from Evonik Industries, Struktol SCA985 from Struktol Company), 3-thiocyanatopropyl-triethoxysilane (e.g., Si264 from Evonik Industries), γ-mercaptopropyl-trimethoxysilane (e.g., VP Si163 from Evonik Industries, Struktol SCA989 from Struktol Company), γ-mercaptopropyl-triethoxy ... Si263), zirconium dineoalkanolatodi(3-mercapto)propionato-O, N,N'-bis(2-methyl-2-nitropropyl)-1,6-diaminohexane, S-(3-(triethoxysilyl)propyl)octanethioate (e.g., NXT coupling agent from Momentive, Friendly, WV), and / or other silica coupling agents known to those of skill in the art.

[0044] Alternatively or additionally, the carbon black particles can be treated with other silica modifiers or hydrophobizing agents. Such agents can be covalently or non-covalently bonded to the carbon black particles. Representative hydrophobizing agents include silicone fluids. Non-limiting examples of useful silicone fluids include polydimethylsiloxane, polydiethylsiloxane, phenylmethylsiloxane copolymers, fluoroalkylsiloxane copolymers, diphenylsiloxane-dimethylsiloxane copolymers, phenylmethylsiloxane-dimethylsiloxane copolymers, phenylmethylsiloxane-diphenylsiloxane copolymers, methylhydrosiloxane-dimethylsiloxane copolymers, polyalkylene oxide modified silicones, D3, D4, and D5 type cyclic polysiloxanes, and the like. Modified silicone fluids such as hydroxyl-terminated siloxanes can also be used.

[0045] Alternatively or additionally, the silica modifier may include a hydrophobizing silane. For example, the hydrophobizing silane may be represented by the formula R 3 4-n Six n where n is 1 to 3 and each R 3 are independently hydrogen, C1-C 18 Alkyl groups, C3-C 18 Haloalkyl groups, and C6-C 14 aromatic groups, each X is independently selected from the group consisting of C-C 18 The alkoxy group or halo. Alternatively or additionally, the silica modifier comprises a silazane. For example, the hydrophobizing agent can be hexamethyldisilazane, octamethyltrisilazane, cyclic silazane, etc. In certain embodiments, the silica modifier comprises a charge modifier, such as one or more of those disclosed in U.S. Patent Application Publication No. 2010 / 0009280, the contents of which are incorporated herein by reference. Alternatively or additionally, the dimethylsiloxane copolymers disclosed in U.S. Patent Application Publication No. 2011 / 0244382, the contents of which are incorporated herein by reference, can be used to treat carbon black particles.

[0046] The carbon black of the present invention can be modified by depositing silicon-containing species such as silica on at least a portion of the surface of the carbon black to coat the carbon black.The carbon black can be silica-coated.Silica coating materials and methods for coating carbon black with silica can include those shown in U.S. Patent Nos. 6,197,274 and 6,541,113, which are incorporated herein by reference in their entirety.The silica coating can partially or completely cover the surface of the carbon black. The carbon black can be oxidized. Suitable oxidizing agents can include, but are not limited to, acids (e.g., nitric acid) and ozone. Coupling agents such as those shown in U.S. Pat. No. 6,057,387, the entirety of which is incorporated herein by reference, or other coupling agents shown herein can be used with the oxidized carbon black. The present invention will be further defined by the following examples, which are intended to be merely exemplary of the present invention. EXAMPLES

[0047] (Example 1) The carbon blacks of the present invention were produced in reactor runs utilizing a multi-stage reactor configuration as shown in Figure 1 or Figure 2. The reactor dimensions and components are outlined in Table 1 below.

[0048] In each run, the primary fuel for the combustion reaction was natural gas introduced into the reactor at near ambient temperature (approximately 77°F), using 120% primary combustion and 100% K +or other Group IA / IIA metal ion concentration was zero (0 ppm) and a total carbon black production feed rate of about 433-282 kg / hr was used. The liquid feed was preheated to 175°C prior to introduction into the reactor. The feed introduction orifices were positioned in an equidistantly spaced annular pattern (axial plane) around the reactor at positions 32 and 42 in Figure 1 and positions 320 and 420 in Figure 2. The feedstock utilized had the properties listed in Table 2 below. [Table 1]

[0049] [Table 2]

[0050] Intermediate quench water, if used, was introduced as a fine spray by a pressurized atomizer. In the reactor of Figure 1, intermediate quench water, if used, was introduced at only one of the two locations shown, 24A or 24B. The carbon black formed in the reaction was then thoroughly quenched with water downstream of the second carbon black-yielding feedstock to form the carbon black of the present invention.

[0051] Additional process conditions, including overall combustion (OAC), feed split between the first and second feed introductions, are shown in Table 3. [Table 3]

[0052] Particle size distribution measurements were performed using a disk centrifuge photosedimentometer, model BI-DCP, manufactured by Brookhaven Instruments, following the ISO 15825 method. Volume-weighted aggregate size distribution (ASD) plots were generated for each of the selected carbon black samples. Table 4 shows the mean diameter (D) of the particle size distribution for runs 1-6 and 8-10. 平均 ), mode diameter (D モード ), D10 , D 50 , D 90 , ΔD 50 , D 75 / D 25 , ΔD 50 / D モード , (D 90 -D 10 ) / D 50 , and the value of formula (1). The value of formula (1) is 133.33 × (ΔD 50 / D モード ) / COAN. Values ​​calculated from equation (1) for several commercially available carbon blacks are also included in Table 4. Commercially available carbon blacks are sold under the trade names VULCAN® M ("VM"), VULCAN® 6 ("V6"), PROPEL® E6 ("PE6"), and VULCAN® 10H ("V10H") (Cabot Corporation).

[0053] [Table 4]

[0054] The physical properties of the carbon blacks of Runs 1-11 are shown in Table 5 along with the physical properties of the commercially available carbon blacks listed above sold under the trade names VULCAN® M ("VM"), VULCAN® 6 ("V6"), PROPEL® E6 ("PE6"), and VULCAN® 10H ("V10H") (Cabot Corporation). The carbon blacks formed in each corresponding run have the iodine adsorption number, OAN, COAN, STSA, BET, and tint strength listed in Table 5. The OAN, COAN, STSA, and BET were determined by the respective methods listed above, the iodine adsorption number was determined by the ASTM D1510 method, and the tint strength was determined by the ASTM D3265 method. In Table 5, the physical properties are reported in nm 3 refers to normal cubic meter, where "normal" is defined as the volume of gas corrected to 0° C. and 1 atm pressure.

[0055] [Table 5]

[0056] (Example 2) Rubber compositions were prepared incorporating selected carbon blacks from Example 1 (Runs / Products 1-11) and one of the commercially available carbon blacks listed in Table 5 (VM, V6, PE6, V10H). The modulus (300%), stiffness (G'10%), and hysteresis loss (maximum tan δ or tan delta) were determined for each modified rubber. In these experiments, the carbon blacks were used in rubber compounds having the complete formulation shown in Table 6 below to study the effect of using the carbon blacks of the present invention in comparison to the aforementioned commercially available carbon blacks as well as carbon blacks commercially available from Cabot Corporation under the trade names VULCAN® 7 ("V7"), CRX™ 1444 ("CRX1444"), and CRX™ 1346 ("CRX1346"). The formulation included N-(1,3-dimethylbutyl)-N'-phenyl- / phenylenediamine, Flexsys, St. Louis, MO ("6PPD"), CALIGHT RPO process oil, Antioxidant DQ ("AO DQ") pellets, Akrochem, Akron, OH, Akrowax™ 5031 beads, Akrochem, Akron, OH. In the final pass, sulfur and the accelerator N-tert-butylbenzothiazole-2-sulfenamide ("TBBS") were added.

[0057] [Table 6]

[0058] The components used in the rubber composition (listed in Table 6) were mixed following three stages of mixing in a BR Banbury 1600 mixer as outlined in Table 7 below. [Table 7] Vulcanization was carried out in a heated press set at 150° C. for a time determined by a conventional rubber rheometer (ie, T90+10% of T90, where T90 is the time to achieve 90% vulcanization).

[0059] The following tests were used to obtain performance data for each modified rubber: 300% Modulus (MPa) was determined according to ASTM D412-06, Standard Test Methods for Carbon Black in SBR-Recipe and Evaluation Procedures. - tan δ was measured using a Rheometrics Dynamic Spectrometer Model ARES-2K at a constant frequency of 10 Hz, constant temperature, and shear mode strain. Strain sweeps were performed at 0°C with double strain amplitudes from 0.1% to 120%. Measurements were made at 10 points per decade and the maximum tan δ measured was reported. The storage modulus G' was determined and reported as part of these measurements of tan δ. G' is often related to the stiffness of the material.

[0060] Performance data from these tests using various carbon black loadings are shown in Tables 8-11. The loadings of the commercial comparison blacks were different but higher than the claimed carbon black loadings to match hardness. [Table 8]

[0061] [Table 9] [Table 10]

[0062] [Table 11]

[0063] As detailed in the results in Tables 8-11, the carbon black of the present invention provides modified rubber compounds with stiffness G'(10%) (MPa) and hysteresis tan δ that are at least about 5% and even at least about 10% greater than rubber compounds containing comparable amounts of VM, PE6, or V6. 最大 The ratio of can provide stiffness and hysteresis. Additionally, as shown by the data in Tables 8-11, the rubber products modified with the carbon black of the present invention have a lower tan δ compared to the rubber products modified with the commercially available carbon black. 最大 and had higher stiffness values.

[0064] Generally, the present invention may further include one or more of the following aspects: Overall, high COAN and low ΔD 50 can increase G' at a given STSA but at the same time lower ΔD 50 These results suggest that high COAN, in combination with STSA and OAN properties, can produce carbon blacks that negate the tradeoff between G' and tan δ (e.g., reducing hysteresis to avoid undesirable loss of stiffness).

[0065] Another embodiment of the carbon black of the present invention has a recited ΔD for COAN value of at least 110 mL / 100 g. 50 / D モード As shown in Figure 1, the aggregate size distribution (ASD), i.e., the width of the ASD distribution, is small and narrow for such high structure carbon blacks. This ASD is narrow for such high structure carbon blacks, and without wishing to be bound by theory, may contribute to the null of the stiffness and hysteresis tradeoff seen in the rubber compositions studied in this invention.

[0066] In one embodiment, the narrowness of the ASD for COAN is expressed as follows: × (ΔD 50 / D モード) / COAN<1. This formula represents the ability to measure the amount of variation in aggregate size distribution. A number less than 1 represents a more controlled or less variable aggregate size distribution, while a value of 1 or greater represents a greater variation in aggregate size distribution, which is typical of conventional high COAN commercial carbon blacks. In other words, if at least some carbon blacks have a high COAN, this will result in an undesirable increase in the variation in aggregate size distribution. Previously, it was difficult to achieve a narrow aggregate size distribution along with the other properties of carbon blacks described herein. The present invention overcomes this difficulty, and the values ​​of less than 1 derived from formula (1) for the carbon blacks of the present invention represent this possibility. The COAN can be increased without increasing the variation in aggregate size. The carbon black of the present invention can have a value from formula (1) of less than 1, or less than 0.99, or less than 0.9, or less than 0.8, or from 0.4 to 0.99, or from 0.45 to 0.85, or from 0.5 to 0.825, or from 0.6 to 0.8, or other values.

[0067] The present invention includes the following aspects / embodiments / features in any order and / or in any combination. 1.80m 2 / g~150m 2 / g range of STSA, an OAN of at least 180 mL / 100 g, and At least 110mL / 100g COAN Carbon black having the following properties: 2.90m 2 / g~150m 2 / g range of said STSA, at least 180 mL / 100 g of said OAN; and At least 120mL / 100g of said COAN The carbon black of any preceding or following embodiment / feature / aspect, having the property 3.100m 2 / g~150m 2 / g range of said STSA, at least 200 mL / 100 g of said OAN; and At least 120mL / 100g of said COAN The carbon black of any preceding or following embodiment / feature / aspect, having the property 4. The carbon black of any preceding or following embodiment / feature / aspect, wherein the carbon black has a ratio of Iodine Adsorption Number / STSA in the range of 0.9 to 1.5. 5. The carbon black of any preceding or following embodiment / feature / aspect, wherein the ratio of iodine adsorption number / STSA is in the range of 1 to 1.3. 6. The carbon black of any preceding or following embodiment / feature / aspect, having an iodine adsorption number in the range of 90 mg / g to 220 mg / g. 7. The carbon black of any preceding or following embodiment / feature / aspect, wherein the OAN is at least 200 mL / 100 g. 8. The carbon black of any preceding or following embodiment / feature / aspect, wherein the OAN is at least 220 mL / 100 g. 9. The carbon black of any preceding or following embodiment / feature / aspect, wherein the OAN is in the range of 200 mL / 100 g to 310 mL / 100 g. 10. The carbon black of any preceding or following embodiment / feature / aspect, wherein the COAN is at least 130 mL / 100 g. 11. The carbon black of any preceding or following embodiment / feature / aspect, wherein the COAN is in the range of 120 mL / 100 g to 150 mL / 100 g. 12. Carbon black, 70m 2 / g~200m 2 The carbon black of any preceding or following embodiment / feature / aspect, having a BET surface area in the range of 0.1% by mass and 0.1% by mass of carbon black. 13. Carbon black, 90m 2 / g~200m 2 The carbon black of any preceding or following embodiment / feature / aspect, having a BET surface area in the range of 0.1% by mass and 0.1% by mass of carbon black. 14. Carbon black, 70m 2 / g~130m2 The carbon black of any preceding or following embodiment / feature / aspect, having a BET surface area in the range of 0.1% by mass and 0.1% by mass of carbon black. 15. Carbon black has a ΔD of 75 nm or less 50 The carbon black of any preceding or following embodiment / feature / aspect, 16. Carbon black, 133.33 × (ΔD 50 / D モード 2. The carbon black of claim 1, further comprising the property that: 17. Carbon black has an L of 29 Å or less a The carbon black of any preceding or following embodiment / feature / aspect, having a crystallite size. 18. The carbon black of any preceding or following embodiment / feature / aspect, wherein the carbon black has a primary particle size of 24 nm or less. 19. The carbon black of any preceding or following embodiment / feature / aspect, wherein the carbon black has a primary particle size of about 12 nm to 24 nm. 20. Carbon black has a thermal conductivity of about 1 mJ / m 2 ~about 15mJ / m 2 The carbon black of any preceding or following embodiment / feature / aspect, having a surface energy in the range of 21. The carbon black of any preceding or following embodiment / feature / aspect, wherein the carbon black has a tint strength in the range of 110% to 140%. 22. A modified carbon black, comprising the carbon black of any preceding or following embodiment / feature / aspect that has been modified by at least one of: at least one coupling agent attached to the surface of the carbon black, at least one chemical group attached to the surface of the carbon black, at least one chemical group adsorbed to the surface of the carbon black, a surface coating, a surface oxidation, or any combination thereof. 23. The modified carbon black of any preceding or following embodiment / feature / aspect, wherein the at least one chemical group is at least one organic group. 24. A rubber compound comprising at least one polymer and carbon black of any preceding or following embodiment / feature / aspect. 25. A vulcanized rubber compound comprising at least one polymer and carbon black of any preceding or following embodiment / feature / aspect.

[0068] The present invention may include any combination of these various features or embodiments described above and / or below, as described in sentences and / or paragraphs. Any combination of features disclosed herein is considered part of the present invention, and no limitation is intended with respect to features that may be combined.

[0069] Applicants specifically incorporate the entire contents of all cited documents in this disclosure. Furthermore, when an amount, concentration, or other value or parameter is given as a range, a preferred range, or a list of values ​​higher than a preferred value and / or lower than a preferred value, this is to be understood as specifically disclosing all ranges formed from any pair of any upper range or preferred value and any lower range or preferred value, regardless of whether the range is separately disclosed. When a range of numerical values ​​is given herein, unless otherwise indicated, the range is intended to include its endpoints, and all integers and fractions within the range. It is not intended that the scope of the present invention be limited to the specific values ​​recited when defining the range.

[0070] Other embodiments of the invention will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered as exemplary only, with a true scope and spirit of the invention being indicated by the following claims and equivalents thereof. Yet another aspect of the present invention may be as follows. (1) 80m 2 / g~150m 2 / g range of STSA, OAN of at least 180 mL / 100 g; At least 110mL / 100g COAN Carbon black having the following properties: (2) 90m 2 / g~150m 2 / g range of said STSA, at least 180 mL / 100 g of said OAN; At least 120mL / 100g of said COAN The carbon black according to [1] above, having the following properties: (3) 100m 2 / g~150m 2 / g range of said STSA, at least 200 mL / 100 g of said OAN; At least 120mL / 100g of said COAN The carbon black according to [1] above, having the following properties: [4] The carbon black according to the above [1], having an iodine adsorption number / STSA ratio in the range of 0.9 to 1.5. [5] The carbon black according to [4] above, wherein the ratio of iodine adsorption number / STSA is in the range of 1 to 1.3. [6] The carbon black according to [4] above, wherein the iodine adsorption number is in the range of 90 mg / g to 220 mg / g. [7] The carbon black according to [1] above, wherein the OAN is at least 200 mL / 100 g. [8] The carbon black according to [1] above, wherein the OAN is at least 220 mL / 100 g. [9] The carbon black according to [1] above, wherein the OAN is in the range of 200 mL / 100 g to 310 mL / 100 g.

[10] The carbon black according to [1] above, wherein the COAN is at least 130 mL / 100 g.

[11] The carbon black according to [1] above, wherein the COAN is in the range of 120 mL / 100 g to 150 mL / 100 g. (12) 70m 2 / g~200m 2 The carbon black according to [1] above, having a BET surface area in the range of 1 / g. (13) 90m 2 / g~200m 2 The carbon black according to [1] above, having a BET surface area in the range of 1 / g. (14) 70m 2 / g~130m 2 The carbon black according to [1] above, having a BET surface area in the range of 1 / g.

[15] ΔD of 75 nm or less 50 The carbon black according to [1] above, having

[16] 133.33 × (ΔD 50 / D モード ) / COAN<1.

[17] L less than 29 Å a The carbon black according to [1] above, having a crystallite size.

[18] The carbon black according to [1] above, having a primary particle size of 24 nm or less.

[19] The carbon black according to [1] above, having an average primary particle size of about 12 nm to 24 nm.

[20] Approximately 1mJ / m 2 ~about 15mJ / m 2 The carbon black according to [1] above, having a surface energy in the range of

[21] The carbon black according to [1] above, having a specific tint strength in the range of 110% to 140%.

[22] A modified carbon black comprising the carbon black according to [1] above, which has been modified by at least one of the following: at least one coupling agent bonded to the surface of the carbon black according to [1] above; at least one chemical group bonded to the surface of the carbon black according to [1] above; at least one chemical group adsorbed to the surface of the carbon black according to [1] above; a surface coating; a surface oxidation; or any combination thereof.

[23] The modified carbon black according to

[22] , wherein the at least one chemical group is at least one organic group.

[24] A rubber compound comprising at least one polymer and the carbon black described in [1].

[25] A vulcanized rubber compound comprising at least one polymer and the carbon black described in [1].

Claims

1. 90m 2 / g ~ 150m 2 / g range of STSA, an OAN of at least 190 mL / 100 g, wherein said OAN is determined by ASTM D2414-13a; and It has a COAN property of at least 110 mL / 100 g, and 133.33×(ΔD 50 / D モード ) / COAN < 1; Carbon black.

2. At least 120 mL / 100 g of said COAN 2. The carbon black according to claim 1, having the following properties:

3. 100m 2 / g ~ 150m 2 / g range of said STSA, at least 200 mL / 100 g of said OAN; and At least 120 mL / 100 g of said COAN 2. The carbon black according to claim 1, having the following properties:

4. 4. The carbon black according to claim 1, having an iodine adsorption number / STSA ratio in the range of 0.9 to 1.

5.

5. 5. The carbon black according to claim 4, wherein the iodine adsorption number is in the range of 90 mg / g to 220 mg / g.

6. 70m 2 / g to 200m 2 The carbon black according to any one of claims 1 to 5, having a BET surface area in the range of 1 / g.

7. ΔD of 75 nm or less 50 The carbon black according to any one of claims 1 to 6, having a formula:

8. The carbon black according to any one of claims 1 to 7, having a tint strength in the range of 110% to 140%.

9. 9. A modified carbon black comprising the carbon black of any one of claims 1 to 8 that has been modified by at least one of the following: at least one coupling agent attached to the surface of the carbon black of any one of claims 1 to 8; at least one chemical group attached to the surface of the carbon black of any one of claims 1 to 8; at least one chemical group adsorbed to the surface of the carbon black of any one of claims 1 to 8; a surface coating; a surface oxidation; or any combination thereof.

10. A rubber compound comprising at least one polymer and the carbon black according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Improved rubber composition

    JP1989275643A

  • Hard high structure carbon black

    JP1994136289A

  • Rubber composition

    JP1994256579A

  • Rubber composition

    JP1995324144A

  • Rubber composition

    JP1996259733A